2018
DOI: 10.1016/j.jstrokecerebrovasdis.2017.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fabry Disease in Young Patients with Stroke in Argentina

Abstract: FD was identified in 1 patient (.3%) in this first Latin American study. The patient presented with a late-onset oligo-symptomatic form of the disease. A large number of nonpathogenic mutations were present in our cohort, and it is essential that they not be mistaken for pathogenic mutations to avoid unnecessary enzyme replacement treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
2
16
0
3
Order By: Relevance
“…In a Canadian cohort of cryptogenic ischemic vascular events, the prevalence of Fabry disease was low, estimated to be around 0.3% [3,4]. Almost similar findings were reported in other studies among different populations [5,6,7]. This probably indicates homogeneous results among different populations despite variation in ethnic backgrounds and study-related methodologies.…”
Section: Discussionsupporting
confidence: 82%
“…In a Canadian cohort of cryptogenic ischemic vascular events, the prevalence of Fabry disease was low, estimated to be around 0.3% [3,4]. Almost similar findings were reported in other studies among different populations [5,6,7]. This probably indicates homogeneous results among different populations despite variation in ethnic backgrounds and study-related methodologies.…”
Section: Discussionsupporting
confidence: 82%
“…One hemizygote with low AgalA activity had a renal biopsy without findings compatible with FD. 31 36 We identified four studies conducted in 2362 patients with neurologic disorders (three in patients with stroke 37,38,40 and one in patients with stroke or unexplained white matter lesions or vertebrobasilar dolichoectasia 39 ). All four hemizygotes had decreased AgalA activity: three with a range 10-33 nmol/L/mg protein in leucocytesref.…”
Section: Screening Of Populations Considered At High Risk For Fdmentioning
confidence: 99%
“…We reviewed 19 studies [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121] on high-risk screening in individuals with central neurological manifestations (Table 3). Most of these studies reported screening in individuals with idiopathic strokes.…”
Section: High-risk Screening For Fd In Individuals With Central Neurological Manifestationsmentioning
confidence: 99%